A rare case of primary thyroid amyloidosis. (2018) - Cannizzaro, M.A.; Lo Bianco, S.; Saliba, W.; D'Errico, S.; Pennetti Pennella, F.; Buttafuoco, G.; Provenzano, D.; Magro, G.
Highlights: The patient complained of dysphagia and respiratory difficulty. He had not shown any signs of systemic amyloidosis. The patient underwent total thyroidectomy. Based on morphological and histochemical features, the diagnosis of "amyloid goiter" was rendered. Abstract: Introduction: Amyloid goiter is due to the deposition of amyloid in the thyroid, resulting with enlargement of the gland and compressive symptoms. Case: We herein present a case of a 45-year-old male patient who complained of a big swelling in the neck. Ultrasound showed an enlarged thyroid gland with mediastinal involvement. The multinodular appearance was consistent with the diagnosis of multinodular goiter. He had a history of multiple myeloma but no sign of systemic amyloidosis. Discussion: Thyroid gland was removed and the histopathological examination revealed a diffuse deposition of amyloid associated with metaplastic lipomatosis of the stroma. Conclusions: The treatment of choice in patients with amyloid goiter is total thyroidectomy to solve compression symptoms.